2003
DOI: 10.1021/jo0267091
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functionalized Piperidinones

Abstract: A versatile, stereoselective synthesis of 5-hydroxypiperidinones with substituents at N1, C3, and C6 has been developed. The sequence involves ring-closing metathesis of a diene amide and epoxidation of the resulting alkene, followed by base-mediated elimination, and finally hydrogenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Other N -substituted allyl amines, 2f and 2g , were also found to be suitable partners in reaction with 1a for the formation of ene-ynes 3l and 3m , respectively, which subsequently underwent Pauson–Khand reaction to provide the corresponding bicyclo­[5.3.0]­decanes 4l and 4m in good yield (entries 3 and 4, Table ). The chiral amine 2h , obtained from phenyl alanine, was tested for the present strategy by reacting with MBH-acetate 1a . Gratifyingly, the reaction provided the expected 5/7-bycyclic compound 4n in 72% yield with >99% diastereoselectivity through the ene-yne intermediate 3n (entry 5, Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other N -substituted allyl amines, 2f and 2g , were also found to be suitable partners in reaction with 1a for the formation of ene-ynes 3l and 3m , respectively, which subsequently underwent Pauson–Khand reaction to provide the corresponding bicyclo­[5.3.0]­decanes 4l and 4m in good yield (entries 3 and 4, Table ). The chiral amine 2h , obtained from phenyl alanine, was tested for the present strategy by reacting with MBH-acetate 1a . Gratifyingly, the reaction provided the expected 5/7-bycyclic compound 4n in 72% yield with >99% diastereoselectivity through the ene-yne intermediate 3n (entry 5, Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Morita–Baylis–Hillman acetates 1a – 1c , 3-allyl- N -Boc-oxindole ( 2c ), and the chiral amine 2h have been prepared using the literature procedures. Analytical data of all of these compounds were correlated with the corresponding reported data.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…All reactions proceeded smoothly to afford the anti -S N 2‘ products 48 − 50 . After removal of the DMB group under acidic conditions, the resulting lactams were converted into the corresponding ( Z )-alkene dipeptide isosteres using Guibé's methodology 5a. These represent cis -peptide bond equivalents, indicating that our novel synthetic methodology for the preparation of DKP mimetics may also afford a potential strategy for the stereoselective synthesis of ( Z )-alkene dipeptide isosteres.…”
Section: Resultsmentioning
confidence: 99%
“…These include synthetic protocols that employ the ring-closing metathesis or palladium-catalyzed carbonylation as key reactions (Scheme ). Ring-closing metathesis of bisolefinic amide 5 with Grubbs' ruthenium alkylidene complexes yielded the desired DKP mimetics 2 , where the stereochemical outcome depends on the stereochemistry of the requisite metathesis substrate 5 , which was obtained by coupling between enantiomerically pure 1-substituted prop-2-enylamines 3 and 2-substituted but-3-enoic acids 4 . Alternatively, Knight et al have reported the enantioselective synthesis of 3,6-dihydro-1 H -pyridin-2-ones 7 by Pd-catalyzed decarboxylative carbonylation of 5-vinyloxazolidin-2-ones 6 , which were synthesized from the corresponding α-amino aldehydes .…”
Section: Introductionmentioning
confidence: 99%
“…Medium-sized unsaturated lactams are important components of natural products that possess many and varied biological properties, including antitumor, antibiotic, antithelmintic , and insecticidal activity . They also find wide use in organic synthesis and as a basis of peptidomimetic scaffolds that accurately define and stabilize the biologically active conformations of peptides and proteins . As such, a good deal of effort has focused on developing general synthetic approaches to simple monocyclic lactams based on ring closure, ring expansion, cycloaddition, and fragmentation reactions .…”
mentioning
confidence: 99%